2020
DOI: 10.1186/s13287-020-01758-9
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of human dental pulp stem cells ameliorates diabetic polyneuropathy in streptozotocin-induced diabetic nude mice: the role of angiogenic and neurotrophic factors

Abstract: Background: Dental pulp stem cells (DPSCs) have high proliferation and multi-differentiation capabilities that maintain their functionality after cryopreservation. In our previous study, we demonstrated that cryopreserved rat DPSCs improved diabetic polyneuropathy and that the efficacy of cryopreserved rat DPSCs was equivalent to that of freshly isolated rat DPSCs. The present study was conducted to evaluate whether transplantation of cryopreserved human DPSCs (hDPSCs) is also effective for the treatment of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 35 publications
0
25
0
Order By: Relevance
“…Dental pulp stem cells (DPSCs) are also a source of NCLSCs that have multilineage differentiation potential, immunomodulatory properties, and high regenerative capability 126,127 . As a result, DPSCS can be utilized to treat a broad spectrum of disorders, 126,127 including PNI, 128,129 retinal injury, diabetes, cerebral ischemia, myocardial infarction, muscular dystrophy, and neurological diseases 128,130,131 . Indeed, in several case studies and preliminary clinical trials, the transplantation of DPSCs has proven to be a safe and effective therapeutic strategy, 127 indicating that DPSCs are a promising cell source for tissue regeneration and the treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Dental pulp stem cells (DPSCs) are also a source of NCLSCs that have multilineage differentiation potential, immunomodulatory properties, and high regenerative capability 126,127 . As a result, DPSCS can be utilized to treat a broad spectrum of disorders, 126,127 including PNI, 128,129 retinal injury, diabetes, cerebral ischemia, myocardial infarction, muscular dystrophy, and neurological diseases 128,130,131 . Indeed, in several case studies and preliminary clinical trials, the transplantation of DPSCs has proven to be a safe and effective therapeutic strategy, 127 indicating that DPSCs are a promising cell source for tissue regeneration and the treatment of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the clinical application of hDPSCs in Alzheimer’s disease, corneal reconstruction, and cerebral ischemia [ 28 , 29 , 30 ]. hDPSC transplantation into skeletal muscles ameliorates diabetic polyneuropathy at 4 weeks post-transplantation [ 22 ]. In this study, a single transplantation of hDPSCs into diabetic mice ameliorated the sciatic nerve motor nerve, sensory nerve, sciatic nerve blood flow, and CPTs, even after 16 weeks of transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…hDPSC-CM promotes the neurite outgrowth of DRG neurons. The administration of VEGF- and NGF-neutralizing antibodies inhibits the effects of hDPSC transplantation on the MNCV and SNCV [ 22 ]. Our previous study revealed the critical role of the secreted factors from DPSCs [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations